2007
DOI: 10.2165/00044011-200727110-00002
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Third-Line Treatment with Alemtuzumab for Chronic Lymphocytic Leukaemia

Abstract: Third-line treatment of eligible patients with alemtuzumab was found to be $NZ15,303 less costly than FCR per patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…QALYs are particularly useful for conditions for which treatment is not curative but palliative, such as cancer. For example, the incremental cost per QALY gained was a key endpoint in recent cost-effectiveness evaluations in CLL and chronic myeloid leukaemia (CML) [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…QALYs are particularly useful for conditions for which treatment is not curative but palliative, such as cancer. For example, the incremental cost per QALY gained was a key endpoint in recent cost-effectiveness evaluations in CLL and chronic myeloid leukaemia (CML) [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…Eight studies examining the costs or cost-effectiveness of alemtuzumab, ipilimumab, sipuleucel-T, or ofatumumab, were included in the final analyses. [25][26][27][28][29][30][31][32] Table 2 summarizes findings of review articles identified from the phase I search regarding the cost-effectiveness of therapeutic cancer vaccines and immunotherapy in the current literature. As shown, rituximab combined with chemotherapy was considered to be costeffective for non-Hodgkin's lymphoma (NHL) when compared to chemotherapy alone.…”
Section: Resultsmentioning
confidence: 99%
“…24 There were four cost papers identified from the phase II search, covering alemtuzumab (for chronic lymphocytic leukaemia, CLL), ipilimumab (for metastatic melanoma) and sipuleucel-T (for castration-resistant prostate cancer, CRPC) (table 3). [25][26][27][28] Scott et al reported that alemtuzumab was cost saving ($11,181/patient) in New Zealand when compared to chemotherapy. 27 Jarkowski et al reported that ipilimumab with dose rounding was cost saving ($7,503/patient) in the United States when compared to ipilimumab without dose rounding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, determination of the cost-effectiveness of alemtuzumab was warranted. One published economic evaluation of alemtuzumab in CLL was found [23]. In that study, intravenous alemtuzumab was compared to FCR in refractory CLL.…”
Section: Introductionmentioning
confidence: 99%